A structure of persuasion in Galatians: epistolary and rhetorical appeal in an aural setting - D. Mitternacht (Acta Theologica)
The purpose of this paper is to ponder the reception of the Letter to the Galatians in an aural setting. How did the first recipients react, what can we expect that they remembered after having listened to the letter? Are there structural elements in the letter that would have aided the aural reception of the letter? In four readings, the investigation traces textual indicators of interaction and emotion, compares their locations with epistolary and rhetorical structure-analysis and identifies a structure of persuasion. The focus on listeners is motivated by the supposition that illiteracy was the rule rather than the exception among those to whom the letter to the Galatians was sent. The different readings reveal a structure of persuasion with a realistic prospect to succeed as a mnemonic device in an aural setting on a macro-structural level. Situational passages (1:6-10; 3:1-5; 4:8-20; 5:2-12 and 6:12-13), together with recurring affirmations of Christ and Paul as embodiments of faithfulness and commitment in suffering, imprint on the aural memory of the first listeners a concern for an imitatio Christi crucifixi.